2020
DOI: 10.32601/ejal.834676
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of strategy instruction: Young learners’ listening performance and strategy use

Abstract: This paper reports on an exploratory investigation into the impacts of implicit instruction of listening strategies on strategy use and listening performance of young EFL learners in Turkey. Data from 34 lower-intermediate learners of English in two-4 th grade-classes in a primary school were analysed to investigate to what extent their employment of listening strategies varied after 12-week-strategy instruction integrated into their listening activities, and whether there was any change in their awareness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…A similar finding was also reported in Nguyen's (2018) and Irgin and Erten's (2020) study. After receiving LSI integrated into the syllabus, the participants shared that they felt more confident in their ability to comprehend English and were satisfied with it the listening course.…”
Section: Affective Aspectssupporting
confidence: 91%
See 3 more Smart Citations
“…A similar finding was also reported in Nguyen's (2018) and Irgin and Erten's (2020) study. After receiving LSI integrated into the syllabus, the participants shared that they felt more confident in their ability to comprehend English and were satisfied with it the listening course.…”
Section: Affective Aspectssupporting
confidence: 91%
“…On the one hand, this finding supports many researchers such as Oxford (1990Oxford ( , 2017, Little (2007); Griffiths (2013); Irgin and Erten (2020) in asserting that autonomy has a very strong relationship with learning strategies. In turn, Oxford (2003Oxford ( , 2017 noted many times that autonomy contributes to learners' use of strategies, and the use of strategies also strengthens autonomy.…”
Section: Behavioral Aspectssupporting
confidence: 83%
See 2 more Smart Citations
“…Our analytical review revealed relatively fewer studies that focused on receptive skills, listening having even less emphasis than reading. Irgın and Erten's (2020) EFL young learners, for instance, showed improvements in their listening performance and strategy use after a 12-week strategy instruction, as well as a self-reported increase in their awareness of listening, self-confidence, and willingness to use listening strategies. Özgen and Gündüz's (2020) experimental study, on the other hand, underlined the pedagogical benefits of using authentic captioned sitcoms on EFL learners’ listening comprehension.…”
Section: Classroom Processes and Instructional Practicesmentioning
confidence: 99%